Cold rolling behaviour and textural evolution in AISI 316L austenitic stainless steel - Chowdhury, Sandip Ghosh; Das, Samar; De, P.K. (Acta materialia, 2005)
The present paper deals with the evolution of microstructure and texture of a 316L austenitic stainless steel during cold rolling. With increasing rolling reductions, different deformation mechanisms become active. TEM observations show the presence of deformation twinning. With increasing strain the volume fraction of twin increases. At higher degrees of reduction, there is evidence that flow localization takes place and there is formation of shear bands. The material initially shows Cu-type texture, i.e., Cu {1 1 2}〈1 1 1〉, Bs {1 1 0}〈1 1 2〉 with a spread towards Goss {0 1 1}〈1 0 0〉. With the progress of rolling, the Cu {1 1 2}〈1 1 1〉 component diminishes and the other two components increase their intensity during rolling. At higher strain levels, there are additional texture components, {1 1 1}〈 u v w〉. The evolution of texture is correlated with the associated deformation mechanisms.